2014
DOI: 10.1364/oe.22.016000
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of adaptive optics system in satellite-to-ground coherent optical communication

Abstract: Adaptive optics (AO) systems can suppress the signal fade induced by atmospheric turbulence in satellite-to-ground coherent optical communication. The lower bound of the signal fade under AO compensation was investigated by analyzing the pattern of aberration modes for a one-stage imaging AO system. The distribution of the root mean square of the residual aberration is discussed on the basis of the spatial and temporal characteristics of the residual aberration of the AO system. The effectiveness of the AO sys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 11 publications
0
16
0
Order By: Relevance
“…With the aperture increasing continuously, the wave front aberration can degrade the communication performance inevitably, especially for the coherent optical link. An adaptive system installed in the large aperture receiver on the ground can compensate the wave front aberration effectively [24]. To improve the reliability of the communication system in further, a coherent multiple apertures diversity receiving system will be investigated.…”
Section: Discussionmentioning
confidence: 99%
“…With the aperture increasing continuously, the wave front aberration can degrade the communication performance inevitably, especially for the coherent optical link. An adaptive system installed in the large aperture receiver on the ground can compensate the wave front aberration effectively [24]. To improve the reliability of the communication system in further, a coherent multiple apertures diversity receiving system will be investigated.…”
Section: Discussionmentioning
confidence: 99%
“…The mixing efficiency is approximate to the Strehl ratio of the far field of the received beam for homodyne detection, and it is defined by the ratio of the far field encircled energy and the diffraction limited encircled energy [18]. The intensity distribution on the focal plane before correction (detail view) is shown in Fig.…”
Section: The Ber Of the Coherent Fso Systemmentioning
confidence: 99%
“…Li evaluated the performance of the coherent FSO system employing quad- rature array phase-shift keying modulation over the maritime atmosphere with AO system based on SHWFS for atmospheric turbulence compensation [15]. C. Liu and J. Huang analyzed the improvement of BER for the coherent FSO system with AO system based on SHWFS through numerical simulation and experimental data of the 1.8 m telescope with a 127-subaperture SHWFS, under different D/r0 [16][17][18][19]. However, the SHWFS was so sensitive to laser scintillation that the performance was limited seriously for a coherent FSO system.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the inherent high utilization of the frequency spectrum and the robustness to the intersymbol-interference (ISI), orthogonal frequency division multiplexing (OFDM) technology has been widely studied in optical fiber communications and attracted interests in FSO systems to boost transmission capacity [7]- [9]. Meanwhile, as that coherent detection combined with advanced digital signal processing (DSP) provides higher receiver sensitivity, greater immunity to noise and higher spectrum efficiency than DD [10], it has great potential applications in LEO-StG optical communications and has been paid more and more attentions [11]. Furthermore, result in [12] have shown that the polarization fluctuation caused by the atmospheric turbulence is rather small over the StG link, which validates that the polarization multiplexing is more attractive in LEO-StG optical communications to improve capacity without increasing the bandwidth.…”
Section: Introductionmentioning
confidence: 99%